LEGAL ANALYSIS OF TRAFFIC ACCIDENTS INVOLVING LARGE VEHICLES WITH CONTENTER LOADS IN INDONESIA BASED ON LAW NUMBER 22 OF 2009 CONCERNING TRAFFIC AND ROAD TRANSPORTATION CASE STUDY: 87/PID.SUS/2021/PN MRS - Muhammad Irsyadul Anam; Muh. Jufri Ahmad (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study analyzes the implementation of Law Number 22 of 2009 on Road Traffic and Transportation (UU LLAJ) as a multi-layered accountability framework (layered liability) in major vehicle accident cases, focusing on the gap between the law's legislative intent (ratio legis) and the Judge's main legal consideration (ratio decidendi) in Decision Number 87/PID.SUS/2021/PN MRS. The findings reveal a significant disparity between the law's requirement for multi-party accountability (criminal, civil, and administrative) and empirical law enforcement practices that tend to centralize fault (culpa) on the driver (driver-centric), overlooking potential corporate structural negligence related to Article 48 of UU LLAJ and Over Dimension and Over Loading (ODOL) practices, due to difficulties in corporate criminal prosecution. In the examined case, the Judge found the Defendant (truck driver) guilty of gross negligence (culpa lata) for failing to secure a broken-down truck left on a dark roadway for nine hours without warning signs, an omission that served as the dominating factor in the victim's death (Article 310 paragraph 4). Despite this, the Judge applied substantive justice by imposing a lighter sentence of one year and six months based on humanitarian considerations. The study concludes that reform in technical accident investigation and the consistent application of corporate criminal liability are urgently needed to create structural deterrence and achieve comprehensive justice